Water usage management, Thailand - Muangthong, Somphinith; Moungprasert, Chuti; Chontanaswat, Pongsak (Food Agricultural Sciences and Technology, 2019)
Water use in Thailand is probable to increase rapidly due to economic and social changes, change in water usage activities, changes in government investment policies increase in the number of tourists, and climate change. The increase in water use results in water shortage which leads to insufficient water to meet the demand. Therefore, short-term and long-term water resource managements need the water demand information from the physical factors of the area. The water allocation in accordance with the needs of each water user is provided. Although the government agencies have already published water usage information via the website, the water usage data in form that truly reflects the water image and quantitative use at all levels are not fully presented nor up to date. This study presents the previous water shortage problem, assessment of water demand for primary activities, information related to government water use assessment and, proposes guidelines for water use assessment that are consistent with the changing context of Thailand. The assessment of water demand should be adjusted in accordance with the rapidly changing situation and show the concentration of spatial water usage activities at all levels for a comprehensive assessment and the slightest mistake